Implementation of the Problem Based Learning Model to Increase the Activity and Learning Outcomes of Students in the Digestive System Material and the Human Respiratory System Class XI MAN 2 Tanah Datar - Sri Wahyuni; Syamsurizal; Irdawati; Violeta; Suci Fajrina (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the model Problem based Learning inÂ  improve results and learning activities in biology learning system material digestion and the human respiratory system. The type of research carried out is in accordance with the problem researched is study action class (Classroom action research). The population in this study were students of class XI MIPA MAN 2 Tanah Datar who were enrolled in the 2022/2023 academic year. The sample in this study were students in class XI MIPA 1 and XI MIPA 2 MAN 2 Tanah Datar. Data collection techniques used in this study were observation, questionnaires, documentation and field notes. The data analysis technique used to analyze activity data and student learning outcomes is the percentage technique and the t test. The results of this study indicate that the average student learning outcomes have increased from cycle I (68.55 %) to cycle II (86.20%). In line with the learning activities of students also increased from cycle I (48 %) to cycle II (77%). The conclusion of this study is that the Problem Based Learning (PBL) learning model can increase the activity and learning outcomes of students in biology class XI IPA MAN 2 Tanah Datar.